2017
DOI: 10.3892/ijo.2017.4221
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of programmed-death ligand in the human head and neck squamous cell carcinoma microenvironment is mediated through matrix metalloproteinase-mediated proteolytic cleavage

Abstract: Recurrent and/or metastatic head and neck squamous cell carcinoma (R/M HNSCC) is a devastating malignancy with a poor prognosis. According to recent clinical studies, tumour growth can be effectively reduced and survival can be improved by blocking the programmed death receptor-1 (PD-1)/programmed death-ligand 1 (PD-L1) pathway. PD-L1 expression has been proposed as a potential causative mechanism, as HNSCC is highly immunosuppressive. However, anti-PD-1 treatment is beneficial only for certain patients. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 52 publications
0
34
1
1
Order By: Relevance
“…Consistently our results also show an upregulation of MMP9, MMP13 and MMP19 in response to MSA. MMPs have recently been shown to degrade PDL1 ( 20 ), thus the decreased protein levels of PDL1 after MSA treatment of CP70 cells found in the current study, may likely be explained via the induction of MMPs that subsequently degrade PDL1. A further study is warranted to confirm if the mechanism by which MSA downregulates PDL1 is via MMPs.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Consistently our results also show an upregulation of MMP9, MMP13 and MMP19 in response to MSA. MMPs have recently been shown to degrade PDL1 ( 20 ), thus the decreased protein levels of PDL1 after MSA treatment of CP70 cells found in the current study, may likely be explained via the induction of MMPs that subsequently degrade PDL1. A further study is warranted to confirm if the mechanism by which MSA downregulates PDL1 is via MMPs.…”
Section: Discussionmentioning
confidence: 61%
“…The downregulation of PDL1 however did not occur at the transcriptional level as the mRNA expression of PDL1 was drastically increased upon MSA treatment (Figure 3B ). To further understand the mechanism of PDL1 downregulation, the expression of matrix metalloproteineases (MMP9, MMP13, and MMP 19) were analyzed, as MMPs have been reported to degrade PDL1 ( 20 ). All the three MMP's were significantly upregulated in response to MSA (Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…Recombinant MMP‐13 and MMP‐7 were shown to degrade intact purified PD‐L1 without observation of low‐molecular‐weight fragments suggesting that the degradation may be occurring at the PD‐1 binding domain. In addition, treatment of human squamous cell carcinoma cells OSC‐20 with a specific inhibitor of MMP‐13 (CL82198) restored PD‐L1 expression suggesting that the shedding/cleavage of PD‐L1 by MMP‐13 may play a role in the protective effect against invasion and metastasis (Hira‐Miyazawa et al, ). Recently, it was also shown that treatment with anti‐PD‐L1 antibody resulted in a decrease of both mRNA and protein levels of MMP‐2 and MMP‐9 in pancreatic cancer and liver metastases in a syngeneic pancreatic cancer mouse model (Fig.…”
Section: Functional Roles Of Mmps and Adams In The Tumor Microenvironmentioning
confidence: 99%
“…Notably, soluble PD-L1 may be generated from ectodomain shedding mediated by either matrix metalloproteinases (MMPs) or a disintegrin and metalloproteases (ADAMs). Additionally, soluble PD-L1 may be produced by alternative splice variants omitting transmembrane domain (Dezutter-Dambuyant et al, 2016;Hira-Miyazawa et al, 2018;Aguirre et al, 2020;Orme et al, 2020;Romero et al, 2020). Although soluble PD-L1 is found in human serum and is regarded as a liquid biopsy predictor, whether soluble PD-L1 can deliver a regulatory signal through PD-1 remains elusive (Gu et al, 2018;Takeuchi et al, 2018;Abu Hejleh et al, 2019;Asanuma et al, 2020).…”
Section: Exopd-l1 As a Biomarker For Efficacy Of Anti-pd-1/pd-l1 Therapymentioning
confidence: 99%